EFFECTIVENESS OF THE USE OF DIETARY FEEDS FOR ALIMENTARY DYSTROPHY IN DOGS - Хілобок, Олександр; Маценко, Олена (SWorldJournal, 2023)
The paper presents the results of complex treatment of dogs with nutritional dystrophy, which was accompanied by malabsorption syndrome and manifested by impaired digestion and absorption of nutrients from the intestine into the blood. In order to restore